2020
DOI: 10.1016/j.encep.2020.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Racing and crowded thoughts in mood disorders: A data-oriented theoretical reappraisal

Abstract: Objectives. -Speed of thought is a central phenomenon in mood disorders. We aimed to provide an update on the topic ten years after a first narrative review published on racing and crowded thoughts in mood disorders. This update is based on recent publications, including recent works of our group. Methods. -Narrative review based on publications from the last ten years including publications of our group and a systematic research of references on PubMed.Results. -The traditional dichotomist view of racing vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Racing thoughts also predict a greater likelihood of conversion to BD after a first depressive episode (Diler et al, 2017; Fiedorowicz et al, 2011; Zeschel et al, 2013). It is noteworthy that racing thoughts, although primarily related to mood disorders, are not specific to BD and can be found in other psychiatric conditions which share symptoms of mood alterations, such as anxiety disorder, attention deficit/hyperactivity disorder and sleep disorders (Bertschy, Weibel, Giersch, & Weiner, 2020). A study on a healthy population suggests that milder forms of racing thoughts can be associated to sub-clinical mood instability (Weiner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Racing thoughts also predict a greater likelihood of conversion to BD after a first depressive episode (Diler et al, 2017; Fiedorowicz et al, 2011; Zeschel et al, 2013). It is noteworthy that racing thoughts, although primarily related to mood disorders, are not specific to BD and can be found in other psychiatric conditions which share symptoms of mood alterations, such as anxiety disorder, attention deficit/hyperactivity disorder and sleep disorders (Bertschy, Weibel, Giersch, & Weiner, 2020). A study on a healthy population suggests that milder forms of racing thoughts can be associated to sub-clinical mood instability (Weiner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms underlying racing thoughts may generalize to perception. Racing thoughts were first studied phenomenologically based on qualitative analyses of BD patients' descriptions (Bertschy et al, 2020; Piguet et al, 2010). Since then, significant advances have been made to capture this complex phenomenon, notably via the development of the Racing and Crowded Thoughts Questionnaire (RCTQ) (Weiner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“… 45 In the same study, using a principal component analysis, we found that a single component explained 55.9% of the variance with major and exclusive contributions from 9 items. Therefore, as suggested by one of our recent studies, 32 This component did not support a dualistic view of racing thoughts versus crowded thoughts and suggested instead that subjective thought overactivation encompasses an overproduction of thoughts but also thoughts getting muddled, as well as the unrestrained/uncontrollable nature of thought flow. …”
Section: Racing Thoughtsmentioning
confidence: 54%
“… 48 It has been shown that subsyndromal hypomanic symptoms appear to enhance psychosocial functioning in bipolar-II patients. 65 As we developed elsewhere, 32 in hypomanic states, it is possible that an inverse U-shaped relationship between racing thoughts and well-being/functioning. In mild hypomania, the cognitive ability to process new thoughts is well balanced with the speed of thinking: one is therefore not overwhelmed and the experience is that thinking is fluid and pleasant.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation